Primary amelanotic malignant melanoma of the small intestine diagnosed by esophagogastroduodenoscopy before surgical resection - Suganuma, Takanori (Springer Japan, 2013)
A 67-year-old man, presenting with anemia and suspected gastric cancer, was referred to our hospital, where he underwent esophagogastroduodenoscopy (EGD). Biopsy revealed densely populated semi-circular cells with abundant cytoplasm that were positive for S-100 protein, melanoma antigen, and HMB-45, resulting in a diagnosis of malignant melanoma. A gastrointestinal barium study for further exploration demonstrated a filling defect 6 cm in size at the ligament of Treitz. Follow-up EGD of this finding revealed an ulcerated, half-circumferential lesion with a distinct ulcer mound extending from the ascending part of the duodenum to the jejunum, and additional biopsy also indicated malignant melanoma. Computed tomography scans showed wall thickening from the ascending part of duodenum to the proximal jejunum, whereas positron emission tomography revealed accumulation at the upper gastric body, the duodenum to the jejunum, and the left adrenal gland. Systemic exploration of the patient, including the skin, anus, and eyeballs, revealed no other lesions, and primary small intestinal malignant melanoma with metastasis to the stomach and adrenal gland was diagnosed. Partial duodenojejunectomy, partial gastrectomy, and left adrenalectomy were performed, and adjuvant chemotherapy with dacarbazine, nimustine hydrochloride, and vincristine sulfate was administered. No postoperative recurrence has been observed in the past 3 years.